Psychological Empowerment and Employees’ Performance: Mediating role of Innovative Behavior in Nepalese Organizations - Adhikari, Yogendra (PYC Nepal Journal of Management, 2023)
This study attempts to analyze the complex relationship that exists between three important HR dimensions: psychological empowerment, innovative behavior, and employees’ performance in Nepalese organizations. Understanding the factors that lead to improved employee performance in today’s dynamic workplaces is essential for organizational success. Psychological empowerment has been identified for its role to inspire the employees and increase their work commitment whereas the innovative behavior is essential for organizational innovation. The study uses a quantitative approach with a broad sample of 607 employees from the hotel, insurance, and banking industries in Nepal. To analyze and interpret findings, the study adopted a descriptive, correlational and explanatory research design approach for which the study performed the reliability, validity, factor, correlation and regression analysis with the use of the tools like Exploratory Factor Analysis (EFA), and Confirmatory Factor Analysis (CFA). This study investigates how psychological empowerment influences innovative behavior and subsequently impacts overall employee performance. The study is significant for identifying the role of innovative behavior as a mediator in the relationship between psychological empowerment and employees’ performance. These findings offer valuable theoretical insights to researchers and practical benefits to practitioners by emphasizing the importance of fostering psychological empowerment and innovative behavior to improve employees’ performance as well as the overall performance of the organizations.